2003
DOI: 10.1002/ajmg.a.10197
|View full text |Cite
|
Sign up to set email alerts
|

Turner phenotype in a girl with a 45,X/46,XX/47,XX,+18 mosaicism

Abstract: We report a girl with Turner syndrome phenotype, whose karyotype on amniocyte culture was 45,X, while cytogenetic analysis on peripheral blood lymphocytes showed the presence of a mosaic chromosome constitution with three different cell lines: 45,X[5]/46,XX[3]/47,XX,+18 [35]. No signs of trisomy 18 were observed and a follow up during childhood revealed normal psychomotor development. Parental origin and mechanism of formation were studied using high polymorphic microsatellites and Quantitative Fluorescent PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Most of cases consist of monosomy X and trisomy 21 [Harada et al, 1998]. Only six cases involving monosomy X and trisomy 18 have been reported so far [Schinzel et al, 1974; Serville et al, 1977; Franceschini et al, 1996; Genuardi et al, 1999; Schubert et al, 2002; Lorda‐Sanchez et al, 2003]. Little is known about patient phenotype, evolution, and mechanisms leading to this double aneuploidy.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Most of cases consist of monosomy X and trisomy 21 [Harada et al, 1998]. Only six cases involving monosomy X and trisomy 18 have been reported so far [Schinzel et al, 1974; Serville et al, 1977; Franceschini et al, 1996; Genuardi et al, 1999; Schubert et al, 2002; Lorda‐Sanchez et al, 2003]. Little is known about patient phenotype, evolution, and mechanisms leading to this double aneuploidy.…”
Section: To the Editormentioning
confidence: 99%
“…We showed that this rearrangement was due to the loss of a maternal chromosome X and the gain of a maternal chromosome 18. Association of monosomy X and trisomy 18 is a rare condition and, to our knowledge, only six cases have been reported since 1974 [Schinzel et al, 1974; Serville et al, 1977; Franceschini et al, 1996; Genuardi et al, 1999; Schubert et al, 2002; Lorda‐Sanchez et al, 2003] (Table II). Phenotype is extremely variable.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We report on a case of a prenatally diagnosed constitutional mosaicim for trisomy 18 and monsomy X, associated with a very mild phenotype. Review of the literature cites seven previous cases, [Schinzel et al, 1974; Serville et al, 1977; Franceschini et al, 1996; Genuardi et al, 1999; Schubert et al, 2002; Lorda‐Sanchez et al, 2003; Picone et al, 2006] however, only two were diagnosed prenatally [Schubert et al, 2002; Picone et al, 2006]. Both prenatally diagnosed cases were terminated due to severe congenital anomalies.…”
Section: To the Editormentioning
confidence: 99%
“…The difficulty lay in not being able to predict outcome with the amniocentesis results. The limited literature available indicates that children with this type of mosaicism usually have a combination of features found in Trisomy 18 and Turner syndrome [Schinzel et al, 1974; Serville et al, 1977; Franceschini et al, 1996; Genuardi et al, 1999; Schubert et al, 2002; Lorda‐Sanchez et al, 2003; Picone et al, 2006]. The cases with mild or no mental retardation usually have more of a Turner syndrome phenotype.…”
Section: To the Editormentioning
confidence: 99%